P1575 Preserved myocardial work efficiency after transcatheter aortic valve implantation-induced left bundle branch block. (17th January 2020) - Klaeboe, L G; Brekke, P H; Haugaa, K H; Edvardsen, T
Abstract: Background Left bundle branch block (LBBB) frequently complicates transcatheter aortic valve implantation (TAVI), but may not induce classical mechanical dyssynchrony typically observed in heart failure patients with LBBB. Non-invasive estimated myocardial work by pressure strain-loops is a novel method for evaluation of left ventricular (LV) performance including loading conditions and identifies responders to cardiac resynchronization therapy. Assessment of myocardial work in TAVI-induced LBBB has, however, not been performed earlier. Purpose We aimed to evaluate myocardial performance in TAVI-induced LBBB by myocardial work. Methods Patients with severe aortic stenosis (AS) and normal ventricular conduction undergoing transfemoral TAVI were included. TAVI-induced LBBB was defined according to strict ECG criteria. In addition to standard echocardiographic parameters, we performed speckle tracking echocardiography (STE) within 2 days post procedure. Post-procedural myocardial work was estimated by commercially available software, combining LV strain by STE and a non-invasively estimated LV pressure curve. Peak systolic LV pressure was assumed to be equal to the sum of peak arterial cuff pressure and mean aortic valve pressure gradient. The proportion of constructive work relative to the sum of wasted and constructive work was expressed as myocardial work efficiency (Figure). A global work efficiency < 90 % was considered abnormal according to the recently published EACVI NORRE study. Results We included 109 consecutive patients undergoing TAVI (83 ± 7 years old, 54 % women, logistic Euroscore 16 ± 10) with severe AS (valve area 0.7 ± 0.2 cm2, mean transvalvular gradient 54 ± 18 mmHg), QRS duration 94 ± 10 ms, and a relatively preserved LV ejection fraction (54 ± 9%). New-onset LBBB was observed in 28 patients (26 %) after TAVI. Although post-procedural myocardial work efficiency was slightly better in patients who retained normal ventricular conduction than those with TAVI-induced LBBB (93.6 ± 2.5% vs 91.2 ± 3.4%, p = 0.004), both groups of patients had global myocardial work efficiency within the normal reference range. Conclusions Patients with TAVI-induced LBBB have preserved work efficiency despite gross electrical block satisfying strict ECG criteria. The reduced myocardial work efficiency in TAVI-induced LBBB was within the reference range of normal in the recently published EACVI NORRE study. The preservation of myocardial work in TAVI-induced LBBB may explain why LBBB as a complication to TAVI does not necessarily imply poor prognosis.